Factors associated with hypertension among cocoa farmers in Sawangaoha Village Kodeoha District North Kolaka Regency - Risti Risti; La Ode Muhamad Sety; Devi Savitri Effendy (Journal of Law, Administration, and Social Science, 2026)
Hypertension is a common health problem and a major risk factor for cardiovascular disease. Among cocoa farmers, hypertension is influenced by factors such as genetic history, smoking habits, stress, and physical activity. These factors contribute to an increased risk of high blood pressure; therefore, understanding them is important for the prevention and control of hypertension. This study aimed to determine the factors associated with hypertension among cocoa farmers in Sawangaoha Village, Kodeoha District, North Kolaka Regency. This study used an analytic observational design with a cross-sectional approach. The sample consisted of 140 respondents selected using consecutive sampling. Data were analyzed bivariately using the Chi-Square test with a significance level of 95% (α = 0.05). The results showed a significant relationship between genetic history and hypertension (p-value = 0.000), smoking habits and hypertension (p-value = 0.002), stress and hypertension (p-value = 0.000), as well as physical activity and hypertension (p-value = 0.028). Based on these findings, it can be concluded that genetic history, smoking habits, stress, and physical activity are associated with the occurrence of hypertension. Therefore, prevention and control efforts are needed, focusing on reducing smoking habits, managing stress, and increasing physical activity to lower the risk of hypertension.